Pengaruh Formulasi Kadar Protein dan Kalsium pada MP-ASI Kacang Tunggak dan Beras Merah terhadap Uji Organoleptik pada Ibu Bayi dan Uji Daya Terima pada Bayi - Qorry Aina; Bayu Irianti (Universitas Muhammadiyah Semarang, 2020)
Background: The prevalence of stunting toddlers in Indonesia is still high. The causes of stunting include the low nutritional value of food consumed by infants. Foods that are rich in nutrients include cowpea and brown rice. Objective: to determine the acceptability and protein and calcium content of porridge with the addition of cowpea and rice through organoleptic testing. Method: this type ofresearch is quasi-experimental. Data collection through organoleptic test on the baby’s mother and acceptance test in baby. Addition of cowpea and brown rice are X1 cowpea 100% brown rice 50% and X2 cowpea 50% and brown rice 100% Analysis of organoleptic test data on porridge using Mann Whitney. Results: Statistical test results showed that the use of cowpea and brown rice affected the color of the porridge (p=0.00) and the taste of the porridge (p=0.04). The use of cowpea and brown rice had no effect on the aroma of porridge (p=0.06), texture (p=0.93) and preference level (p=0.94). Results acceptance porridge with formula X2 more acceptable than X1 because have a higher average and less limp. The highest content of pro-tein and calcium in porridge at X1 is 3.29% and 70.40 mg / kg. Conclusion: the use of cowpea and brown rice in MP-ASI baby porridge affected the organoleptic test results in the color category, and he taste of the porridge.Keywords: cowpea, brown rice, weaning food